The Problem of Feral Hogs and the Challenges of Providing a Weak‐Link Public Good. Issue 3 (5th October 2020) - Ellis, Sean F.; Masters, Mark; Messer, Kent D.; Weigel, Collin; Ferraro, Paul J.
Abstract: Feral hogs are an invasive species in the United States annually inflicting 1.5 billion in damages. Although interest in mitigating this grows, control spans properties and jurisdictions, creating challenges. Because landowners and local governments cannot capture the benefits of control that accrue beyond their boundaries, they generally underinvest. Worse, the weakest contributors constrain efforts. To offer insights into this problem, we synthesized studies on best management practices, invasive species, and weak‐link public goods. We also provide estimates of farmers' willingness‐to‐pay for control efforts, finding that they require financial assistance. Together, this suggests that more investment is necessary to manage feral hogs.